2011
DOI: 10.1016/j.nmd.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Muscle satellite cells from GRMD dystrophic dogs are not phenotypically distinguishable from wild type satellite cells in ex vivo culture

Abstract: Duchenne muscular dystrophy is a neuromuscular degenerative disorder caused by the absence of dystrophin protein. It is characterized by progressive muscle weakness and cycles of degeneration/regeneration accompanying chronic muscle damage and repair. Canine models of muscular dystrophy, including the dystrophin-deficient golden retriever muscular dystrophy (GRMD), are the most promising animal models for evaluation of potential therapies, however canine-specific molecular tools are limited. In particular, few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
8
0
4
Order By: Relevance
“…When compared to cells expanded on human IgG, expanding cells on Delta-1 ext -IgG did not increase the percentage of cells expressing syndecan 4, a marker of satellite cells and satellite cell-derived myogenic cells in culture ( Figure 4B) (Table 1) [17]. In contrast, the CXCR4 receptor, which has a critical role in muscle regeneration [16], showed increased RNA and protein levels in cells expanded on Delta-1 ext -IgG ( Figure 3C and 4A), however, the percentage of CXCR4 expressing cells did not increase (Table 1), indicating a higher abundance of CXCR4 per cell.…”
Section: Activation Of Notch Signaling Inhibits Canine Myogenic Diffementioning
confidence: 98%
“…When compared to cells expanded on human IgG, expanding cells on Delta-1 ext -IgG did not increase the percentage of cells expressing syndecan 4, a marker of satellite cells and satellite cell-derived myogenic cells in culture ( Figure 4B) (Table 1) [17]. In contrast, the CXCR4 receptor, which has a critical role in muscle regeneration [16], showed increased RNA and protein levels in cells expanded on Delta-1 ext -IgG ( Figure 3C and 4A), however, the percentage of CXCR4 expressing cells did not increase (Table 1), indicating a higher abundance of CXCR4 per cell.…”
Section: Activation Of Notch Signaling Inhibits Canine Myogenic Diffementioning
confidence: 98%
“…Cassano et al demonstrated that ventricle-derived CPCs from golden retriever muscular dystrophy (GRMD) dogs showed impaired self-renewal and cardiomyogenic differentiation in vitro and in vivo when compared to those from healthy dogs [53]. In comparison, a recent study showed that there were no obvious alterations to cell biology observed between satellite cells isolated from wild-type or GRMD dystrophic dogs, as determined in vitro by proliferation capacity, clonogenicity, motility, and expression of terminal differentiation proteins [54].…”
Section: Figmentioning
confidence: 99%
“…Satellite cells from dystrophic fibers have been shown to have markedly diminished doubling times and decreased capacity for myogenic differentiation . This decline in satellite cell function may be a result of the dystrophic muscle environment, not from any intrinsic abnormalities, because a recent study found no difference between satellite cell physiology in Golden Retriever muscular dystrophy and wild‐type cells . However, this dysfunction, no matter the cause, does not allow for the usual muscle hypertrophy in response to exercise and mechanical overloading, in which there is satellite cell activation and proliferation, as well as muscle angiogenesis and release of the growth factors IGF‐1 and vascular endothelial growth factor (VEGF)…”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 99%